2007
DOI: 10.1016/j.ydbio.2007.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a functions in planar cell polarity regulation in mice

Abstract: Planar cell polarity (PCP) refers to the polarization of cells within the plane of a cell sheet. A distinctive epithelial PCP in vertebrates is the uniform orientation of stereociliary bundles of the sensory hair cells in the mammalian cochlea. In addition to establishing epithelial PCP, planar polarization is also required for convergent extension (CE); a polarized cellular movement that occurs during neural tube closure and cochlear extension. Studies in Drosophila and vertebrates have revealed a conserved P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
393
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(422 citation statements)
references
References 56 publications
14
393
2
3
Order By: Relevance
“…Unlike Cecr2, all the core PCP genes tested have also been found expressed in the sensory hair cells themselves (Wang et al, 2005;Jones and Chen, 2007;Seifert and Mlodzik, 2007). However, Wnt5a expression also appears in the cochlear floor and not the hair cells (Qian et al, 2007). The latter suggests that Cecr2 may play a role in cells controlling signals that act externally on the hair cells to provide orientation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Unlike Cecr2, all the core PCP genes tested have also been found expressed in the sensory hair cells themselves (Wang et al, 2005;Jones and Chen, 2007;Seifert and Mlodzik, 2007). However, Wnt5a expression also appears in the cochlear floor and not the hair cells (Qian et al, 2007). The latter suggests that Cecr2 may play a role in cells controlling signals that act externally on the hair cells to provide orientation.…”
Section: Discussionmentioning
confidence: 97%
“…Although associated with canonical Wnt signaling, Lrp6 is necessary for Xenopus convergent extension (Tahinci , 2007), yet the exencephalic mice are of normal size, similar to Cecr2. Finally, mutation of Wnt5a results in inner ear defects and neural tube defects: of 34 Wnt5a null animals, 1 had craniorachischisis and 3 had exencephaly (Qian et al, 2007). Therefore, the presence of exencephaly rather than craniorachischisis is within the spectrum of PCP phenotype, although it may be indicative of a secondary or uncharacterized aspect in the pathway.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we utilised Wnt5a, a Wnt ligand protein that is known to signal via the non-canonical Wnt signalling pathway and stimulate the activation of Rac in cultured cells 17,25,40 . Time-dependent Rac activation induced by Wnt5a was attenuated by the knockdown of Daple (Fig.…”
Section: Daple Enhances the Activation Of Racmentioning
confidence: 99%
“…Ror2 has been shown to act as a receptor or co-receptor for Wnt5a (Oishi et al, 2003;Mikels and Nusse, 2006;Nishita et al, 2006). In fact, both Ror2-and Wnt5a-mutant mice showed similar skeletal, cardiovascular, genital and inner ear abnormalities that are caused at least partly by disrupted planar cell polarity and convergent extension movements during development (Qian et al, 2007;Yamamoto et al, 2008). It has been shown that Ror2 mediates Wnt5a signaling by activating the Wnt/JNK pathway and inhibiting the b-catenin-TCF pathway (Oishi et al, 2003;Mikels and Nusse, 2006).…”
Section: Introductionmentioning
confidence: 99%